CLASSROOM ACTION RESEARCH: PENERAPAN STRATEGI BELAJAR NOTE-TAKING, DISCUSSION, REFLECTIVE (NDR) UNTUK MENINGKATKAN HASIL BELAJAR MAHASISWA IPA - Sabtiawan, Wahyu Budi (Jurnal Pendidikan Matematika dan IPA, 2018)
AbstractOne of the difficulties of science students is learning abstract topics, such as Topic of Atom, Ion, and Molecule. This study aims to solve the difficulty using a learning strategy of Note-Taking, Discussion, Reflective (NDR). Specifically, the purpose of this study is to implement the NDR strategy for increasing students' learning outcomes. The research design is classroom action research. Methods of data collection include observation, tests, and interviews. The results of the study indicate that the implementation of Note taking-Discussion-Reflective strategy can increase the learning outcomes through the implementation of 2 research cycles where in each cycle there are three stages, namely, planning, action, and reflection. The average scores increased from cycle 1 to cycle 2 by 4.2% and a minimum score of completeness of 75 has been achieved in cycle 2. The implementation of learning was at a good and excellent level during cycles 1 and 2. In addition, there were four student's positive response to the implementation of NDR strategy, that is related to discussion activities, note-taking, learning opportunities, and working in groups.Keywords: classroom action research, NDR strategy, learning outcome.Â